IMPROVEMENT OF GRADE 1 STUDENTS’ ABILITY OF SMK NEGERI 1 WATUBANGGA IN SPEAKING THROUGH MIND MAPPING STRATEGIES - Wayan Pageyasa (Journal of Indonesian Language Education and Literary, 2016)
Low ability of students in grade 1 SMK Negeri 1 Watubangga in speaking due to less effective and interestingly learning to speak are implemented. Therefore, it applied a creative strategy to solve problems of practical learning to speak it. The strategy is "mind mapping strategy" created by Tony Buzan. Chosen strategy was based on the theoretical and practical considerations. Theoretically, a mind mapping in accordance with the way the brain processes information so that a positive impact on the brain, whereas in practice, the mind mapping easy to implement, does not need to cost, and fun for students. In practice, the strategy mind mapping is realized in five stages of learning, namely (1) the stage of collecting the subject, (2) the stage of framing the conversation, (3) the stage of outlining the specific framework of the talks, (4) the stage of the creation of the framework of the talks, and (5 ) stage speaking from a mind map. The fifth stage was designed learning in a classroom action research (action research).